SNPs of FOXO1 and Their Interactions Contributes to the Enhanced Risk of Diabetes Among Elderly Individuals - Hussain, Sartaj; Yadav, Suraj Singh; Dwivedi, Pradeep; Banerjee, Monisha; Usman, Kauser; Nath, Rajendra; Khattri, Sanjay (DNA and cell biology, 2022)
We have assessed the impact of three single nucleotide polymorphisms (SNPs) of Forkhead Box O1 ( ) and their interaction on susceptibility of type 2 diabetes mellitus in geriatric population from northern India. We genotyped three SNPs (rs2721068, rs17446614, and rs4581585) of gene in 190 elderly individuals with diabetes and 182 unrelated healthy controls of similar ethnicity by using TaqMan SNP assays. SNP-SNP and SNP-environment interactions among polymorphic loci were studied by the multifactor dimensionality reduction (MDR) method. The AA genotype carriers of rs17446614 was associated with the increased susceptibility of diabetes in both adjusted and unadjusted model, whereas rs4581585 was associated with the risk in unadjusted model only. Genotype and minor allele interaction with quantitative parameters revealed that AA genotype of rs17446614 had significantly higher fasting plasma glucose (FPG) in diabetic subjects, also minor allele (A) in patients was positively associated with FPG and glycated hemoglobin. Haplotype T G T increases the risk of diabetes, whereas carrier of haplotypes C G C and C G T were protective. The MDR analysis revealed that interaction of rs17446614 with body mass index (BMI) increased the susceptibility of diabetes. Therefore presence of rs17446614 variant and its interaction with BMI and haplotype T G T modulates the risk of diabetes and can be used as a promising tool for identifying high-risk individuals.